Pariwisata Halal dan Persepsi Loyalitas Wisatawan Muslim terhadap Bali - Putri, Ariana Zakinah; Alawi, Muammar (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2024)
Halal tourism has become one of the fastest growing forms of tourism in Indonesia, especially in Bali. Muslim tourists visiting Bali require facilities and services that are in accordance with Islamic law, such as halal food, sharia-compliant accommodation, and other worship facilities. This study was conducted to examine how halal tourism affects Muslim tourists' perceived loyalty to Bali. The results showed that halal tourism has a positive effect on Muslim tourists' satisfaction and perceived halal value. Muslim tourists who have high satisfaction tend to have higher loyalty to tourist destinations that offer halal facilities. Muslim-friendly facilities also play an important role in increasing the loyalty of Muslim tourists. Muslim tourists who have good Muslim-friendly facilities tend to have higher loyalty towards tourist destinations that offer halal facilities. In this study, researchers also found that perceived halal value and tourist satisfaction have a positive effect on Muslim tourist loyalty. Muslim tourists who have high perceived halal value and high satisfaction tend to have higher loyalty to tourist destinations that offer halal facilities.